Tolerogenic properties of liver macrophages in non‐alcoholic steatohepatitis. (8th January 2020) - Orci, Lorenzo A.; Kreutzfeldt, Mario; Goossens, Nicolas; Rubbia‐Brandt, Laura; Slits, Florence; Hammad, Karim; Delaune, Vaihere; Oldani, Graziano; Negro, Francesco; Clément, Sophie; Gonelle‐Gispert, Carmen; Buhler, Léo H.; et al.
Abstract: Background & Aims: Our understanding of non‐alcoholic fatty liver disease (NAFLD) pathogenesis is improving, but there is still limited data on the function of resident liver macrophages in this context, especially when considering their contribution in dampening liver inflammation. Methods: Liver macrophages were studied in mouse models of prolonged diet‐induced liver steatohepatitis and carbon tetrachloride‐induced liver injury. We assessed liver macrophages phenotype and costimulatory/inhibitory properties upon exposure to lipopolysaccharide or interleukin 4. We did phagocytosis and antigen presentation assays to investigate liver macrophages function as scavengers and immune response initiators. Using immunofluorescence staining, we further determined, in human liver tissue of patients with simple steatosis, non‐alcoholic steatohepatitis and chronic hepatitis B infection, the expression of the co‐inhibitory protein CD274 (Programmed‐death ligand 1) and major histocompatibility complex (MHC) class II. Results: Both in humans and mice, within chronically inflamed fatty livers, liver macrophages acquired immunomodulatory properties by reducing the expression of MHC class II, and by enhancing co‐inhibitory signalling. Liver macrophages circumscribed endotoxin‐mediated inflammatory response by upregulating anti‐inflammatory genes arginase 1 and interleukin‐10. While hepatic macrophages isolated from mice with normal livers were capable of achieving endotoxin tolerance, our results indicated an impairment of this protective mechanism in the presence NASH‐like parenchymal abnormalities. Conclusions: Liver macrophages can achieve endotoxin tolerance, but in the chronically inflamed fatty liver, while they acquire an immunomodulatory phenotype, liver macrophages fail to dampen immune‐mediated damage. Therefore, loss of tolerogenicity induced by ongoing liver insult may be a mechanism contributing to the worsening of NAFLD.